Implementation of Asynchronous Online Competency-based Learning: English for Informatics - Lizda Iswari; Anggara Jatu Kusumawati (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2019)
English for Informatics is a compulsory subject that facilitates students' listening, reading, speaking and writing skills in English. Previously, this course was held in a full face-to-face meeting with a large number of students in a class, which brought some weaknesses, such as difficulty in meeting the learning needs of students with varying abilities and levels of speed resulting in the lack of personal interaction between lecturers and students. This paper describes the implementation of a full asynchronous online learning aimed at building a more personal and creative learning environment. The research model used is an ADDIE development model (Analyse, Design, Development, Implementation, and Evaluation). In preliminary analysis, students' self-assessment and students expectations shows that students need to strengthen their English communication skills both verbally and in writing. Based on the need of students in the study program and the needs after graduation, this course is designed to achieve four competencies, namely English for daily communication, English in the IT field, English for academic purposes, and English for the workplace. Each competency will have an outcome that requires students to study more personally and have a thorough learning experience. Course content is designed to support the competencies needed by fourth-year Informatics students, i.e. research study, student exchange, student internships, and student entrepreneur or community services. The asynchronous online course has been implemented by using the Google Classrooms as the main learning platform and a number of supporting applications, such as Padlet to organize students’ exhibition virtually, Quizlet as virtual flashcards to help students get familiar with important terms, and several interactive tools, such as Google Forms, Quizizz, Mentimeter and Quizlet. The learning evaluation shows that students get improved communication skills in English as well as readiness to choose a concentration in the fourth-year of study.